2020
DOI: 10.3168/jds.2019-18085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of molasses-based liquid feed supplementation to a high-straw dry cow diet on feed intake, health, and performance of dairy cows across the transition period

Abstract: The objective of this study was to determine the effects of adding molasses-based liquid feed to a highstraw dry cow diet on intake, behavior, health, and performance of dairy cows across the transition period. Holstein cows (n = 40) entering their second lactation or greater were enrolled at dry-off (~45 d before expected calving) and assigned to 1 of 2 treatments: a high-straw dry cow total mixed ration (TMR) with either (1) no molasses [CON; n = 20; 10.7% crude protein (CP), 1.45 Mcal/kg of net energy for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
1
11
0
1
Order By: Relevance
“…Besides, the sorting behavior may persist in the fresh period with eventual negative consequences. Havekes et al [32][33][34] very recently proposed a variety of strategies to reduce the sorting behavior in low energy diets in the dry period. In a first experiment [32], they demonstrated that prepartum cows being fed a short chop length (2.54 cm screen) of wheat straw is preferable since it was associated with lower serum BHB concentration in the third week postpartum compared to that in cows fed a long chop length (10.16 cm screen) of wheat straw.…”
Section: Feeding Controlled-energy and Negative Dietary Cation-anion mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the sorting behavior may persist in the fresh period with eventual negative consequences. Havekes et al [32][33][34] very recently proposed a variety of strategies to reduce the sorting behavior in low energy diets in the dry period. In a first experiment [32], they demonstrated that prepartum cows being fed a short chop length (2.54 cm screen) of wheat straw is preferable since it was associated with lower serum BHB concentration in the third week postpartum compared to that in cows fed a long chop length (10.16 cm screen) of wheat straw.…”
Section: Feeding Controlled-energy and Negative Dietary Cation-anion mentioning
confidence: 99%
“…Although a shorter chop length of straw reduced sorting, it did not (completely) eliminate this behavior. In a next set of experiments, Havekes et al [33,34] moisturized the content of high-straw dry cow diets with water or liquid molasses. The hypothesis was that the addition of water to dry-cow diets that are low in moisture would improve DMI and reduce feed sorting, while the addition of liquid molasses will additionally support ruminal cellulolytic microbial growth.…”
Section: Feeding Controlled-energy and Negative Dietary Cation-anion mentioning
confidence: 99%
“…From that group, 20 cows received the diet as described. Another 20 cows received, in addition to the basal diet, 1.0 kg/cow per day (DM basis) of molasses-based liquid supplement, targeting an energy consumption of 22.9 Mcal/cow per day of NE L (Havekes et al, 2020c). The other 20 cows had water added to their dry-cow TMR to reduce the ration DM by ~10% compared with the basal diet (Havekes et al, 2020b).…”
Section: Methodsmentioning
confidence: 99%
“…As it is used in the alcohol and ethanol production and has high microbial activity [18], it is an economical byproduct of sugar factories as it is used in alcohol generation, animal feed preparation, and other food products. Moreover, it is also used as a cattle feed supplement, in yeast propagation, and as a flavoring agent in food products [112]. Biomethanated SW contains many plant nutrients and can thus be used as liquid manure in agriculture [18], and it can also be used for irrigation purposes after making dilutions [86].…”
Section: Benefits Of Using Sugarcane Industries Byproductsmentioning
confidence: 99%